Niat Beli Muslim pada Makanan Korea Bersertifikasi Halal di Indonesia - Maria Oktavianingtias; Istyakara Muslichah (Jurnal Aplikasi Bisnis, 2022)
ABSTRACT This study aims to analyze the factors that influence the purchase intention of Muslim consumers on halal-certified Korean restaurant food in Indonesia. The compiler uses a quantitative approach with a questionnaire compiled using google form. The method used is purposive sampling and convenience sampling to 170 Muslims in Indonesia. To verify the relationship between subjective norms, perceived behavioral control, religiosity, attitudes and buying intentions of Muslims on halal Korean restaurant food, the data was processed using SmartPLS (Partial Least Square). The results showed that only subjective norms and perceived behavioral control had a positive effect on Muslim consumers' purchase intentions. Religiosity affects Muslim attitudes in buying Korean restaurant food, so the results show that religiosity and attitudes do not affect Muslim consumers' buying intentions. This study was distributed randomly without setting strata so that the percentage of respondents' characteristics was not balanced. Due to inconsistent findings from previous studies, this study contributes to the literature on the purchase intention of Muslim consumers on halal-certified Korean restaurant food in Indonesia. And it can also be used as a reference by Korean restaurant business people in Indonesia. Keywords: subjective norm, perceived behavioral control, religiosity, attitude, purchase intention ABSTRAK Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi niat beli konsumen muslim pada makanan restoran Korea bersertifikat halal di Indonesia. Penyusun menggunakan jenis pendekatan kuantitatif dengan kuesioner yang disusun menggunakan google form. Metode yang digunakan adalah purposive sampling dan convenience sampling kepada 170 muslim di Indonesia. Untuk memverifikasi hubungan yang antara norma subyektif, persepsi kontrol perilaku, religiusitas, sikap dan niat beli muslim pada makanan restoran Korea halal, data diolah menggunakan SmartPLS (Partial Least Square). Hasil penelitian menunjukkan bahwa hanya norma subyektif dan persepsi kontrol perilaku berpengaruh positif terhadap niat beli konsumen muslim. Religiusitas mempengaruhi sikap muslim dalam membeli makanan restoran Korea, sehingga hasil menunjukkan bahwa religiusitas dan sikap tidak mempengaruhi niat beli konsumen muslim. Penelitian ini disebarkan secara random tanpa menetapkan strata sehingga persentase karakteristik responden tidak seimbang. Karena temuan yang tidak konsisten dari penelitian sebelumnya, penelitian ini berkontribusi pada literatur tentang niat beli konsumen muslim pada makanan restoran Korea bersertifikat halal di Indonesia. Dan juga dapat dijadikan acuan oleh pelaku bisnis restoran Korea di Indonesia. Kata Kunci: norma subjektif, persepsi kontrol perilaku, religiusitas, sikap, niat beli